ENVIRONMENTAL CONTAMINATION BY SUBSTRATA OF ORE MINING DUMPS, THEIR MONITORING AS WELL AS MEASURES OF REDUCTION - Blumenstein, O.; Pustlauck, F.; Vavelidis, M. (Bulletin of the Geological Society of Greece, 2016)
The main activity fields of the research group “Applied Geoecology“ at the University of Potsdam are the development and tests of complex monitoring systems for water bodies and soils, together with the development of sustainable additives for vegetation restoration on ore mining dumps with extreme substratum parameters. The dump substrata are translocated by surface waters and by aeolian processes to the surroundings affecting soil processes. A field spectrometer has been engineered, which can detect dam substrata in soils. Moreover, various soil additives were developed, enabling the establishment of vegetation on the extreme dump substrata. For all components there have been realised extensive tests in the framework of greenhouse and field experiments under different climate conditions on three continents, on various substrata and with varying plant species. All experiments were successful, even though no additional irrigation and no mineral fertilizer were allowed to be used, in order to realise the idea of a sustainable greening.